Emerging hierachies : processes of stratification and early state formation in the Indonesia archipelago : prehistory and the ethnographic present - Slamet-Velsink, Ina E. (Koninklijk Institut Voor Taal : Land - en Volkenkunde, 1995)
vi, 297 p. : il.; 26 cm.